Analisis Kelayakan Finansial Usaha Ikan Asin Di Desa Batu Belubang Kabupaten Bangka Tengah - Dara Krismonita Agustin (Akuatik: Jurnal Sumberdaya Perairan, 2020)
Batu Belubang Village, Bangka Tengah regency is one of he areas that has the largest number of salted fish processing production houses in Bangka Island. The obstacle in developing of Salted Fish Processing in Batu Belubang Village, is that lack of data and information about the feasibility of accuracy that can be referred in the utilization of these resources optimally. Therefore, the study of financial feasibility of salted fish processing in the Batu Belubang Village, Bangka Tengah regency, is necessary conducted to determine the financial feasibility of salted fish processing. The data compilation methods is done by literature and field study. The data and information that is needed are primary and secondary data. Primary data collecting is got by field survey and interviews with salted fish business owners as many as 54 respondents. Field survey by spreading questionnaires, that involves the questionnaire for profile and cost component of salted fish processing in Batu Belubang Village. The analysis that is applied in this study is descriptive analysis related to salted fish processing business and financial feasibility analysis based on the criteria of total investment value, total cost, total revenue, total income, Benefit Cost of Ratio (BCR), Net Present Value (NPV), Internal Rate of Return ( IRR), and Payback Period (PP).